IMPROVING THE BOOKKEEPING EXPERTISE OF MSME ACTORS THROUGH ACCOUNTING PROCESSING AND REPORTING MENTORING IN THE CURUG BOGOR TOURISM VILLAGE - Sparta Sparta; Indupurnahayu Indupurnahayu; Shanti Lysandra (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, particularly at the local level, such as in Bogor Regency. However, most MSMEs face challenges in financial management, particularly in bookkeeping, which remains rudimentary or even incomplete. This also applies to MSMEs in Curug Tourism Village, Bogor Regency, who are partners in a Community Service (PkM) activity. This activity aims to improve MSMEs' understanding and skills in recording transactions, processing financial data, and preparing simple accounting reports. The method used was participatory training involving outreach, bookkeeping practice, and mentoring. Evaluation was conducted through pre- and post-tests with 29 participants. The results of the activity showed an average increase of 63% in understanding of bookkeeping and simple financial reports. Participants also began to practice separating personal and business finances and preparing simple profit and loss statements. Thus, this mentoring program has proven effective in improving the financial literacy of MSMEs in Curug Tourism Village and contributing to strengthening the village's tourism economy.